Retail Pharmacies and Drug Diversion during the Opioid Epidemic - Janssen, Aljoscha; Zhang, Xuan (American Economic Review, 2023)
This study investigates the role of retail pharmacy ownership in the opioid epidemic. Using data of prescription opioid orders, we show that compared with chain pharmacies, independent pharmacies dispense 39.1 percent more opioids and 60.5 percent more OxyContin. After an independent pharmacy becomes a chain pharmacy, opioid dispensing decreases. Using the OxyContin reformulation, which reduced nonmedical demand but not the legitimate medical demand, we show that at least one-third of the difference in the amount of OxyContin dispensed can be attributed to nonmedical demand. We show that differences in competitive pressure and whether pharmacists own the pharmacy drive our estimates. (JEL G32, I12, L22, L81)